Survival after the implementation of an antimicrobial stewardship program in Pediatric Intensive Care Units in Peru, 2016-2018. - Fonseca Rivera, Irma Carolina (2023)
The indiscriminate use of antimicrobials in pediatric intensive care units (PICU) can complicate the effectiveness of treatments. A tertiary pediatric hospital in Peru implemented an antimicrobial stewardship program (ASP) in its PICU. Our objective was to compare patients' survival before and after the ASP implementation in the study site's five PICU. Methods: We conducted a retrospective cohort observational study. The first group consisted of patients treated from mid-2016 to early 2017 (n=611), and the second group consisted of patients treated from late 2017 to mid-2018 (n=567). Results: Following the implementation of the ASP, we did not identify differences in PICU length of stay but observed variations in the duration of treatment with certain restricted antimicrobials. Additionally, we did not find a difference in survival after implementing the ASP in either crude or adjusted models (adjusted hazard ratio = 1.29, 95% confidence interval = 0.91-1.81, p = 0.14). Conclusion: This is the first study to evaluate changes in survival following the implementation of an ASP in PICU in Latin America. The strength of our study is that it provides evidence on the survival results of pediatric patients treated in a PICU in a Latin American country, after applying an ASP.